Differentiated Borders of Belonging and Exclusion: European Migrants in Rural Areas in Iceland - Skaptadóttir, Unnur Dís; Wojtyńska, Anna; Innes, Pamela (Social Inclusion, 2024)
This article addresses questions of difference, positionality, and belonging from the perspectives of international migrants living and working in rural communities in Iceland. With the recent integration of rural areas into the global economy, small villages and towns have undergone rapid social transformation. The development of new industries and growing tourism in these localities has attracted many international migrants. The share of migrants in the local populations oscillates between 10% to 50%, depending on the town, with the majority coming from Europe. Commonly, they make up the greater part of workers in service jobs and manual labour in rural towns and villages. This article builds on data from ethnographic field research over 15 months in five parts of Iceland located outside of the capital region. Based on the analysis of interviews with migrants, we examine different perceptions of affinity and belonging and explore their experiences of inclusion and exclusion. To what extent do migrants see themselves as part of local communities? How do they narrate their social positions in those places? The discussion highlights how social stratification and hierarchy affect migrants' experiences of inclusion as commonly displayed in the interviews. Furthermore, we elaborate on how notions of relatedness and otherness reflect inherited ideas of Europe and contemporary divergent geopolitical positions.